Iron(0) nanoparticles mediated direct conversion of aryl/heteroaryl amines to chalcogenides via in situ diazotization. Issue 35 (30th August 2017) - Panja, Subir; Maity, Pintu; Kundu, Debasish; Ranu, Brindaban C.
Graphical abstract: Highlights: Direct synthesis of chalcogenides from aryl/hetreoaryl amine. A general synthetic method for all type of sulfides, selenides and tellurides. Avoids isolation and handling of hazardous diazonium salt involving in situ diazotization. Use of inexpensive and nontoxic iron nanoparticles. Tolerance to sensitive functionalities. Abstract: A simple procedure for the synthesis of organo-chalcogenides has been developed by the reaction of aryl/heteroaryl amines with di-aryl/heteroaryl dichalcogenides in the presence of t BuONO and Fe(0) nanoparticles. The reaction proceeds via in situ diazotization followed by chalcogenation. A series of functionalized diaryl/aryl heteroaryl/diheteroaryl/aryl-alkyl selenides, sulfides and tellurides have been obtained by this procedure. Significantly, using this procedure 2, 4-dinitroaniline is converted to (2, 4-dinitrophenyl)(phenyl)selane which is known as thioredoxin reductase (TR) and glutathione reductase (GR) inhibitor. The reaction goes by a radical pathway and a plausible mechanism has been suggested.